2018
DOI: 10.1038/s41467-018-04215-7
|View full text |Cite
|
Sign up to set email alerts
|

Parental haplotype-specific single-cell transcriptomics reveal incomplete epigenetic reprogramming in human female germ cells

Abstract: In contrast to mouse, human female germ cells develop asynchronously. Germ cells transition to meiosis, erase genomic imprints, and reactivate the X chromosome. It is unknown if these events all appear asynchronously, and how they relate to each other. Here we combine exome sequencing of human fetal and maternal tissues with single-cell RNA-sequencing of five donors. We reconstruct full parental haplotypes and quantify changes in parental allele-specific expression, genome-wide. First we distinguish primordial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 40 publications
(57 reference statements)
6
42
0
Order By: Relevance
“…showing loss of the H3K27me3 spot at Wk4 (Tang et al, 2015), and biallelic expression of X-linked genes at Wk7-8 PGCs; however data from earlier stages is not available (Sangrithi et al, 2017;Vértesy et al, 2018). Even though it is not currently possible to conclude whether human XCR occurs as early as shown in pPGCs, our evidence of XCR in pig premigratory pPGCs contrasts with observations in mouse PGCs, where there is limited loss of H3K27me3 (<10%) and Xist (<15%) expression in pre-migratory PGCs; the increase in X:A ratio is first detected in E11.…”
Section: Extensive X Chromosome Reactivation In Pre-migratory Ppgcmentioning
confidence: 99%
“…showing loss of the H3K27me3 spot at Wk4 (Tang et al, 2015), and biallelic expression of X-linked genes at Wk7-8 PGCs; however data from earlier stages is not available (Sangrithi et al, 2017;Vértesy et al, 2018). Even though it is not currently possible to conclude whether human XCR occurs as early as shown in pPGCs, our evidence of XCR in pig premigratory pPGCs contrasts with observations in mouse PGCs, where there is limited loss of H3K27me3 (<10%) and Xist (<15%) expression in pre-migratory PGCs; the increase in X:A ratio is first detected in E11.…”
Section: Extensive X Chromosome Reactivation In Pre-migratory Ppgcmentioning
confidence: 99%
“…In addition, Leydig or steroidogenic cells, macrophages and T cells were also detected [ 119 ]. As expected, germ cells were also sexually dimorphic, being arrested in mitosis in males and meiotically arrested in females [ 123 ]. Novel surface markers were identified for the different types of germ cells, useful for isolating fetal germ cells in meiotic prophase (IL13RA2 + ) and oogenesis (PECAM1 + ) [ 119 ].…”
Section: Single-cell -Omics In Gonadal Development and Maturationmentioning
confidence: 59%
“…However, more recently, it has been shown that about 30% of hPGCs at 4-9 weeks of development still exhibit incomplete XCR, as suggested by the presence of faint perinuclear spots of H3K27me3, a marker of XCI. XCR appears to be more related to the transcriptional signature of the cells rather than to the fetal age [Vértesy et al, 2018]. These observations suggest that, in hPGCs, XCR is heterogeneous and asynchronous, starting from 4 weeks of development onward [Guo et al, 2015;Tang et al, 2015].…”
Section: Mouse and Human Pgcsmentioning
confidence: 83%
“…During postimplantation development, once randomly established, the epigenetic memory determining Xlinked gene silencing is stably inherited through cellular generations. However, in vivo, Xi is reactivated in different cell types like mouse Epi cells [Mak et al, 2004;Borensztein et al, 2017], mouse [Sugimoto and Abe, 2007;Chuva de Sousa Lopes et al, 2008;Mallol et al, 2019] and human [Von Meyenn and Reik, 2015;Vértesy et al, 2018] primordial germ cells (PGCs) and spermatids, during their differentiation into spermatozoa [Ernst et al, 2019].…”
Section: X-chromosome Reactivation During Development and Reprogrammingmentioning
confidence: 99%
See 1 more Smart Citation